Analysis of Waste in Traffic Services on The Surabaya-Gesik Toll Road for Optimization with Lean Service Method at PT Margabumi Matraraya - Tiara Nuriyah Sani; Rr. Rochmoeljati (Universitas KH. Abdul Chalim Mojokerto, 2025)
PT Margabumi Matraraya is a company engaged in the management and operation of the Surabaya-Gresik toll road. This company is responsible for ensuring that the toll road operations run smoothly in accordance with the established service standards. However, in the toll road traffic service process, inefficiencies are still found, such as long customer waiting times, miscommunication, repeated reporting, inefficient routes, less than optimal workforce performance, and excessive service. This study aims to apply the lean service concept to improve efficiency in the toll road service process and provide recommendations for improvements to reduce waste. The methods used include Value Stream Mapping (VSM), Value Stream Analysis Tools (VALSAT), and Root Cause Analysis (RCA). The results of the analysis using VSM showed that the initial service lead time was 265 minutes with non-value-added activities of 5.96%. After the implementation of the improvement recommendations, non-value-added activities were eliminated, so that the lead time was reduced to 228.2 minutes, or equivalent to a time reduction of 13.89%. The proposed improvement recommendations are optimization of communication systems, application of GPS technology for real-time location monitoring, and improvement of training for officers to maximize human resource potential.